TEACHING BY ALPHABET POEM IN ENHANCING STUDENT’S LEARNING STYLE - Muhammad Dalimunte; Sholihatul Hamidah Daulay; Atika Winari Putri (Universitas Putera Batam, 2021)
The aim of this paper is to determine the Alphabet Poem in teaching English. This paper investigates how Alphabet Poem knowledge can help to teach English in English Language Teaching (ELT). The author will conduct a literature review method. The purpose of this paper was to study how alphabet poem can enhancing student’s learning style. The method by using library research and a philosophical or pedagogical approach. The results showed that the role of alphabet poem in teaching English is suitable for learning styles (visual, auditory, and kinesthetic). English students will benefit from the knowledge of alphabet poems and how to teach teaching materials in three different learning styles. The applied linguistic content helps language learners better understand alphabet poems in ELT. The study draws the attention of teachers to be more concerned with the communication condition of students by the creative poem and to the fact that teachers cannot act as expected unless they are each of their learning styles. The teacher brings and teaches the alphabet poem to the students so the students who receive it will also imitate how to make the alphabet poem again so that through learning English it becomes a lesson that is liked by students and students can fluently in English.